Pemanfaatan Kartu Aljabar untuk Meningkatkan Pemahaman Siswa dalam Menyederhanakan Bentuk Aljabar melalui Model Discovery Learning - Siti Rokh Hayati; Rahmat Mulyono (Smart Education, 2023)
Abstract: This study aims to determine the use of algebraic cards to improve students' understanding of simplifying algebraic forms through the Discovery Learning model. The study uses a qualitative descriptive approach from student learning outcomes data and a list of student questions. The research was conducted at SMP Negeri 2 Playen. The research subjects were 32 class VIIB students (14 boys and 18 girls), researchers, and observers. The object of research is the activities during learning and student learning outcomes. The scope of research activities is to examine the use of Algebraic Cards to increase students' understanding of simplifying Algebraic Forms through the Discovery Learning Model. The results showed that class VIIB students experienced an average increase in learning outcomes of 52.56 in learning to simplify algebraic forms by using algebraic cards, the results of the student questionnaires showed that students understood more about how to simplify algebraic forms with algebraic cards. Student understanding has increased, namely the use of Algebraic Cards can increase student understanding in simplifying Algebraic Forms through the Discovery Learning Model.Keywords: algebra cards; algebraic forms; discovery learning; student understanding.Abstrak: Penelitian ini bertujuan untuk mengetahui pemanfaatan kartu aljabar untuk meningkatkan pemahaman siswa dalam menyederhanakan bentuk aljabar melalui model Discovery Learning. Penelitian menggunakan pendekatan deskriptif kualitatif dari data hasil belajar siswa dan daftar pertanyaan siswa. Penelitian dilakukan di SMP Negeri 2 Playen. Subjek penelitian adalah siswa kelas VIIB sebanyak 32 siswa (laki-laki sebanyak 14 dan perempuan sebanyak 18), peneliti, dan observer. Objek penelitian adalah kegiatan selama pembelajaran dan hasil belajar siswa. Ruang lingkup dari kegiatan penelitian adalah meneliti pemanfaatan Kartu Aljabar untuk meningkatkan pemahaman siswa dalam menyederhanakan Bentuk Aljabar melalui Model Discovery Learning. Hasil penelitian menunjukkan bahwa siswa kelas VIIB mengalami kenaikan rata-rata hasil belajar sebesar 52,56 dalam pembelajaran menyederhankan bentuk aljabar dengan memanfaatkan kartu aljabar, hasil dari daftar pertanyaan siswa menunjukkan siswa lebih memahami cara menyederhanakan bentuk aljabar dengan kartu aljabar. Pemahaman siswa mengalami peningkatan yaitu pemanfaatan Kartu Aljabar dapat meningkatkan pemahaman siswa dalam menyederhanakan Bentuk Aljabar melalui Model Discovery Learning.Kata kunci: bentuk aljabar; discovery learning; kartu aljabar; pemahaman siswa,